Opportunities for Applying Artificial Intelligence by Commercial Organizations in Data Security and Cyber Threat Monitoring - Poluyan, Anna; Purchina, Olga; Fugarov, Dmitry (International Journal of Basic and Applied Sciences, 2025)
Intelligent information security methods are approaches based on the use of artificial intelligence and machine learning to increase the level of information protection and combat cyber threats. This is especially important for the financial sector and e-commerce since hackers and fraudsters aim at these companies, and any error by their personnel can lead to large expenses and loss of customer trust. The objective is to determine the opportunities for using AI by commercial organizations in the field of data protection and cyber threat monitoring. To attain this end, the authors conducted an experiment, i.e., they selected 100 companies and divided them into two groups, in each of which they applied AI algorithms to monitor cyber threats, and in one of the groups, they held two online classes on increasing the level of literacy in the field of information security. The study results show that the use of AI algorithms increased protection against cyber threats by 54%, while the efficiency of companies with additional employee training grew by another 27%. The main conclusion is that the use of AI in data security requires substantial data volumes and powerful computing resources. Therefore, a proper plan for the use of AI technologies, combined with personnel training, can significantly increase the protection of information systems and optimize implementation costs.
Keywords: Information; Machine Learning; Network Traffic; Personnel Training; Protection Systems; Security.